Street bankers of Benin - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
On market days in the villages of Benin, travelling bankers criss-cross the roads and alleyways to meet their many and varied clients. Tens of thousands of people entrust small amounts of money to these street bankers and then claim back their...